2013
DOI: 10.7763/ijapm.2013.v3.176
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Influence of Surface Temperature on Fluorine Etching of Silicon

Abstract: Abstract-Molecular dynamics simulation of the reactions between gaseous fluorine atoms and silicon are performed using the development Tersoff-Brenner potential at the temperature from 500K to 1200K. The simulation results show that the Si surface temperature significantly affects the F etching. For instance, as the surface temperature rises up, the numbers of F atoms deposited on and scattered by Si surface decrease, at the same times, the number of the sputtering fluorine atoms and the reactive F atoms with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study by Kim et al 12 found that the preferential sputtering ratio was 1:5.4 at an incident angle φ ¼ 75 deg. 21,22 In this study, Argon atoms were in the form of an inert gas, thus they do not form any bond. 21,22 In this study, Argon atoms were in the form of an inert gas, thus they do not form any bond.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Kim et al 12 found that the preferential sputtering ratio was 1:5.4 at an incident angle φ ¼ 75 deg. 21,22 In this study, Argon atoms were in the form of an inert gas, thus they do not form any bond. 21,22 In this study, Argon atoms were in the form of an inert gas, thus they do not form any bond.…”
Section: Resultsmentioning
confidence: 99%